Diagnosing GORD in Respiratory Medicine - Timms, Chris J.; Thomas, Paul S.; Yates, Deborah H. (Frontiers in Pharmacology, 2011)
Gastroesophageal reflux disease is increasing in prevalence and is associated with several lung diseases such as asthma and COPD. Current diagnostic methods are imperfect, being insensitive, nonspecific, expensive or invasive. An accurate diagnosis of GORD can aid effective treatment with a significant clinical impact. Novel methods such as exhaled breath condensate analysis and electronic nose technology have the potential to improve the accuracy of diagnosing GORD.